(untitled) (Fiep Bulletin - online, 2019)
The present article aims to identify factors that interfere in the quality of life (QoL) of people with Alzheimer’s disease(AD). A systematic bibliographical review was performed using the Methodi Ordinatio of 2016 to 2018. The keywords "Quality ofLife" and "Alzheimer" were used. After the application of the InOrdinatio equation, the 20 relevant articles (17% of the total) wereconsidered, which were read in their entirety. The results indicate as the main factors that interfere positively and that tend toimprove QOL measures are: social interaction, daily activities, physical activities, a friendly and permanent environment, musicalactivities and therapy cognitive. The identified factors that negatively influence the QoL are: depression, apathy, agitation,polypharmacy and increased cognitive impairment of the individual, due to advances in AD.